2012
DOI: 10.2337/db11-0828
|View full text |Cite
|
Sign up to set email alerts
|

Stress Augments Insulin Resistance and Prothrombotic State

Abstract: Stressors contribute to thrombosis and insulin resistance. Since obesity-related adipose inflammation is also involved in these pathological states, we assumed that stress correlates with adipose inflammation. Male mice were subjected to 2-week intermittent restraint stress. Expression of plasma lipids, monocyte/macrophage markers (CD11b, CD68, and F4/80), proinflammatory cytokines (monocyte chemoattractant protein-1 [MCP-1], tumor necrosis factor-α, and interleukin-6), adiponectin, heat shock protein 70.1 (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 49 publications
12
92
1
Order By: Relevance
“…These male mice were then mated with females for 2 days ( Figure S1A). In agreement with previous observations (Depke et al, 2008;Uchida et al, 2012), stress-F0 mice exhibited a reduced body weight gain and increased blood glucose levels, compared with the control-F0 mice (Figures S1B-S1E). However, there were no significant differences in food intake, sperm density, motility, or the pregnancy rates of females between stress-and control-F0 mice (Figures S1F-S1I).…”
Section: Metabolic Phenotypes In Offspring Of Stressed Fatherssupporting
confidence: 80%
See 1 more Smart Citation
“…These male mice were then mated with females for 2 days ( Figure S1A). In agreement with previous observations (Depke et al, 2008;Uchida et al, 2012), stress-F0 mice exhibited a reduced body weight gain and increased blood glucose levels, compared with the control-F0 mice (Figures S1B-S1E). However, there were no significant differences in food intake, sperm density, motility, or the pregnancy rates of females between stress-and control-F0 mice (Figures S1F-S1I).…”
Section: Metabolic Phenotypes In Offspring Of Stressed Fatherssupporting
confidence: 80%
“…Eight-week-old C57BL/6 male mice were subjected to 14 days of daily restraint stress (stress-F0), as previously described (Uchida et al, 2012). These male mice were then mated with females for 2 days ( Figure S1A).…”
Section: Metabolic Phenotypes In Offspring Of Stressed Fathersmentioning
confidence: 99%
“…ber of mechanisms, including activation of inflammatory pathways, serine phosphorylation of the insulin receptor and insulin receptor substrate 1, and increased serum and hepatic triacylglycerol levels [37][38][39]. Our results demonstrated that ASC might improve insulin resistance by modulating inflammation and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 66%
“…Stress-induced autonomic arousal contributes to various cardiovascular-(high blood pressure, increased heart rate) and metabolic alterations that are acknowledged independent risk factors for stroke. It has been shown recently that stress augments insulin resistance and evokes inflammation to increase coagulation factors through adipose tissue derived MCP-1 (Uchida et al 2012). …”
Section: ; Hankey 2006) Exposure To Various Stressors Results Inmentioning
confidence: 99%